Benefit–cost analysis of lane departure warning and roll stability control in commercial vehicles. (September 2017) - Medina-Flintsch, Alejandra; Hickman, Jeffrey S.; Guo, Feng; Camden, Matthew C.; Hanowski, Richard J.; Kwan, Quon
Abstract: Introduction: This paper presents the cost benefits of two different onboard safety systems (OSS) installed on trucks as they operated during normal revenue deliveries. Using a formal economic analysis approach, the study quantified the costs and benefits associated with lane departure warning (LDW) systems and roll stability control (RSC) systems. Methods: The study used data collected from participating carriers (many of these crashes were not reported to state or Federal agencies), and the research team also reviewed each crash file to determine if the specific OSS would have mitigated or prevented the crash. The deployment of each OSS was anticipated to increase the safety of all road users, but impact different sectors of society in different ways. Benefits that were inherent in each group (e.g., industry, society) were considered, and different benefit–cost analyses (BCAs) were performed. Results: This paper presents two BCAs: a BCA focused on the costs and benefits in the carrier industry by implementing each OSS, and a BCA that measured the societal benefits of each OSS. In addition, a BCA for a theoretical mandatory deployment option for each OSS is presented. Conclusions: BCA results for LDW and RSC clearly showed their benefits outweighed their costs for the carrier and society. Practical applications: Cost information is a crucial factor in purchasing decisions in carriers; similarly, regulators must consider the cost burden prior to mandating technologies. The results in this study provide carrier decision makers and regulators with information necessary to make an informed decision regarding RSC and LDW. Highlights: Quantified the costs/benefits of lane departure warning and roll stability control Data were from trucks as they operated during normal revenue deliveries. Carrier and societal costs/benefits are presented. Results showed their benefits outweighed their costs for the carrier and society.